FACTORS OF COFFEE SHOP REVISIT INTENTION AND WORD-OF-MOUTH MEDIATED BY CUSTOMER SATISFACTION - Ayya Sofia; Christian Haposan Pangaribuan; Martinus Fieser Sitinjak (Department of Management - Faculty of Business and Economics. Universitas Surabaya., 2020)
To create value that would surpass the expectation of coffee drinkers is pivotal for coffee shop business. However, only a few businesses are able to provide better and non-homogenous value for the customers. The main factors that would influence customer satisfaction of coffee shops are still yet to be further explored. Hence, this study aims to look into the determinants of customer satisfaction of coffee shops and to examine its influence towards revisit intention and word-of-mouth. Online survey questionnaires were distributed to the customers and 155 samples were gathered from March to June 2018. The findings showed that atmosphere and service quality factors had positive effects on customer satisfaction, while the variety of menu was not significant to the satisfaction, the fact that the satisfied customers would likely have the intention to revisit and spread word-of-mouth